Social exchange theory: Systematic review and future directions - Ahmad, Rehan; Nawaz, Muhammad Rafay; Ishaq, Muhammad Ishtiaq; Khan, Mumtaz Muhammad; Ashraf, Hafiz Ahmad (Frontiers in Psychology, 2023)
Social exchange theory (SET) is one of the most influential theories in social sciences, which has implications across various fields. Despite its usefulness being a typical social transaction, there is a need to look at it from the lens of psychological transactions to further its evolution and identify future directions. After generally reviewing 3649 articles from Social Science Citation Index and Scopus, a total of 46 articles were selected for final review using a comprehensive systematic review approach. We have highlighted the need for further research in psychological transactions, reciprocity principles, exchange relations, and the impact of various factors in the exchange process. Among other exchange rules (social, economic, and psychological) and transactions (social, economic, and psychological), this research provides an elevation platform for the less explored exchange rules in psychological transactions. Among other theories in the social sciences, social exchange theory is a theory that shadows many theories under its umbrella.